Development of a Mobile App for Family Planning Providers. Issue 5 (September 2017) - Halsall, Viannella; Rogers, Jennifer; Witt, Jacki; Song, Sejun; Nguyen, Hoang Duc Huy; Kelly, Patricia
Abstract: Purpose: To provide an overview of lessons learned during the development process of an app for iOS and Android based on national recommendations for providing quality family planning services. Study and Design: After a review of existing apps was conducted to determine whether an app of clinical recommendations for family planning existed, a team of clinicians, training specialists, and app developers created a resource app by first drafting a comprehensive content map. A prototype of the app was then pilot tested using smart tablets by a volunteer convenience sample of women's healthcare professionals. Outcomes measured included usability, acceptability, download analytics, and satisfaction by clinicians as reported through an investigator-developed tool. Results: Sixty-nine professionals tested a prototype of the app, and completed a user satisfaction tool. Overall, user feedback was positive, and a zoom function was added to the final version as a result of the pilot test. Within 3 months of being publicly available, the app was downloaded 677 times, with 97% of downloads occurring on smart phones, 76% downloads occurring on iOS devices, and 24% on Android devices. This trend persisted throughout the following 3 months. Clinical Implications: Clinicians with an interest in developing an app should consider a team approach to development, pilot test the app prior to wider distribution, and develop a web-based version of the app to be used by clinicians who are unable to access smart devices in their practice setting. Abstract : A mobile app for family planning providers was developed and tested. Based on experiences of the development team, clinicians with an interest in developing an app should consider a collaborative approach to development, pilot test the app prior to wider distribution, and develop a web-based version of the app to be used by clinicians who are unable to access smart devices in their practice setting.